Pengaruh Progressive Muscle Relaxation Terhadap Stres Pada Lanjut Usia Dengan Diabetes Melitus Tipe 2 - Aniva, Dwi Reza Wardatul; Astarini, Made Indra Ayu; Manungkalit, Maria (Jurnal Keperawatan Muhammadiyah, 2025)
Elderly with diabetes type 2 are very risk of stress, feelings of stress arises of lifelong diseases process and residence factor. Unresolved stress in elderly has a negative impact on medication and worsens sugar level. And will have an impact on a dractic decline in health or complications. The purpose of this study is to analyzed the effect of PMR on stress in elderly with diabetes type 2 in Nursing Home. This research design used pre-experimental with one-group pre-post test. Independent variable was PMR and dependent variable was stress. The research population was 24, Sample of this study was 20 elderly with diabetes type 2 who were selected used a purposive sampling. Instruments use are Perceived Stress Scale 10 (PSS-10) and Standard Operating Procedures (SOP). PMR given 8 times in a month (twice per week), the duration is 15 minutes. The hypothesis test that was carried out by the stastistic Paired T-Test. The mean pre-post stress value is 19,9 to 7,5. The results of this study is p= 0,000 (p< 0,05) which means that there is a significant PMR effect on stress in elderly with diabetes type 2 in Nursing Home. PMR can reduce cortisol hormone productions. Key words: Diabetes type 2, Elderly, Progressive Muscle Relaxation, Stress